Prospects of the Chinese coal chemical industry in an increasingly carbon-constrained world - Kevin Jianjun Tu (The Oxford Institute for Energy Studies, 2024)
In 2020, the Chinese coal chemical industry processed nearly one quarter of national coal throughput, and accounted for about 5.4 per cent of national CO2 emissions. Yet the coal chemicals' industry ability to limit oil and gas imports is appealing to the Chinese leadership in the context of rising energy security concerns amid geopolitical tensions. This, coupled with strong political desire for investment-driven growth, especially in the post-pandemic economic recovery, suggests that the coal chemical industry could see substantial capacity expansion and emission spikes in the coming decades. Without an appropriate decarbonization strategy in place, further expansion of the industry is expected to contradict China's dual carbon goals of peaking national carbon emissions before 2030, and achieving carbon neutrality before 2060. Despite its large industrial scale, the Chinese traditional coal chemical industry has long suffered from overcapacity, legacy assets, single product structure, and heavy pollution, among other chronic weaknesses. Thus, the coal chemical industry is continuously subject to increasingly stringent and sometimes disruptive energy and environmental regulations but it is also prioritized by key stakeholders, especially local government and the coal industry, to supplement petrochemical manufacturing and climb up the value chain. This paper discusses the current state of play and outlook for China's coal chemical industry. It argues that unless the modern coal chemical industry can outperform its petrochemical counterparts in the net-zero transition (especially after 2030) its long term prospects look increasingly challenging.
Keywords: 330; CCUS; chemicals; China; Coal; decarbonization; Emissions; energy security; Energy Transition; ETS; Gas; Hydrogen; Oil; Petrochemicals